A Sensitive Fluorescent Immunoassay for Prostate Specific Antigen Detection Based on Signal Amplify Strategy of Horseradish Peroxidase and Silicon Dioxide Nanospheres. (20th July 2022) - Li, Lihua; Zhang, Wenzhi; Wei, Yan; Yu, Lizhen; Feng, Dexiang
Abstract : A simple, sensitive, and fluorescent immunoassay for the detection of prostate-specific antigen (PSA) based on horseradish peroxidase and silicon dioxide nanospheres as a signal amplification strategy has been described. In the design, the primary antibody (Ab1 ) of PSA was first immobilized on the 96-well plates via physical adsorption between polystyrene and hydrophobic groups of the antibody molecule. The silicon dioxide nanospheres (SiO2 NSs), with large surface area and good biocompatibility, were loaded with horseradish peroxidase (HRP) and horseradish peroxidase-labeled secondary antibodies (HRP-Ab2 ) as signal amplification systems. In the presence of PSA, a sandwich-type immunocomplex composed of Ab1 -Ag-HRP-Ab2 had been formed. Fluorescence technology was employed to obtain the response signal of the immunoassay in the L -tyrosine and H2 O2 systems. Experiment results showed that a strong and stable fluorescent signal at 416 nm (excitation wavelength: 325 nm) was observed, and the changes in fluorescent intensity were related to the levels of PSA. Under the optimal conditions, the relative fluorescence intensity was linear with the logarithm of PSA concentration from 0.03 to 100 ng·mL −1, with a detection limit of 0.01 ng·mL −1 (at a signal/noise ratio of 3). In contrast to other fluorescent immunoassays, the sandwich-type immunoreaction based on the high binding ELISA plates has the advantages of being simple, stable, and easy to operate, high selectivity, small sample quantity, etc., which can be widely used in the selective detection of a variety of targets, from DNA to proteins and small molecules. Such fluorescent immunoassays should be feasible for the fields of molecular diagnosis and other life science fields in the future.